Hospital Admissions of Huntington's Disease Patients in a Huntington's Disease Centre Between 2011 and 2016: A Retrospective Analysis. Issue 5 (5th May 2022) - Peball, Marina; Heim, Beatrice; Ellmerer, Philipp; Frank, Florian; Busin, Nadia; Galffy, Matyas; Djamshidian, Atbin; Seppi, Klaus
Abstract: Background: Huntington's Disease (HD) is a relentlessly progressive genetic neurodegenerative disorder with characteristic motor, psychiatric, and behavioral abnormalities that inevitably results in severe disability and death. Many patients have multiple hospital admissions during the disease course, but there is limited information which problems lead to hospitalization. Objectives: To assess acute reasons for hospital admissions, discharge routes, and clinical characteristics of HD patients in a retrospective analysis. Methods: We reviewed all medical records of patients with an established diagnosis of Huntington's Disease and hospital admissions between 2011 and 2016 in our local hospital‐based database. Results: There were 135 hospital admissions in 53 HD patients during the review period, representing a median of two admissions per patient. Median duration of hospitalization was seven days. The most frequent reason for admission was a worsening of HD motor symptoms (n = 77, 57.0%) such as chorea, parkinsonism, gait problems, falls, and dysphagia. Psychiatric symptoms related to HD were the second most common reason for admission (n = 58, 43.0%). Infections (including aspiration pneumonia) and traumas/surgical procedures were only responsible for 6.7% and 5.9% of admissions, respectively. Emergency admissions were not common (42.2%), and the majority of patients were able to return to their previous residency upon discharge (85.2%, home or nursing home). Recurrent admissions were associated with worse motor function and functional capacity. Conclusions: Worsening of motor and psychiatric symptoms associated with Huntington's Disease were the most common reasons for hospital admissions. Therefore, our data highlight the importance of optimal symptom control in HD patients.